The Effect of Voltage and Time In Synthesis Manganese Dioxide from Manganese Sulfate Precursor - Eka Fitri Wulandari; Lia Andriyah; Soesaptri Oediyani; Latifa hanum Lalasari; Tri Arini; Nadia Chrisayu Natasha; Fariza Eka Yunita; Ariyo Suharyanto; Eko Sulistiyono (Metalurgi, 2022)
The utilization of manganese dioxide (MnO2) as a cathode material for lithium-ion battery has attract many attentions because of their excellent electrochemical properties which have high theoretical storage capacity of 615 mAh/g. In this study, synthesis of MnO2 was carried out from manganese sulfate (MnSO4) precursor which is a pregnant leach solution from the leaching process of manganese ore from Trenggalek Regency. The electrolysis method has been used in this synthesis of MnO2 in an electrochemical cell consisting of two graphite electrodes with dimensions (16 x 5 x 0,3) cm. The purpose of this study is to determine the effect of voltage and time to particles amount of MnO2, to determine the phase and crystal structure of MnO2 and its morphological microstructure. The electrolysis process was carried out in 2000 ml of MnSO4 solution under constant stirring at 60oC with DC voltage varied by 2, 4, 6 and 8 volt and time varied by 4, 8, 12 and 16 hours. The precipitates formed at anode were separated, then the particles were dried at 110oC for 2 hours. The main contain of MnO2 were analyzed by X-Ray Fluorescence (XRF), the phase and crystal structure were evaluated by X-Ray Diffraction (XRD) and the morphological microstructure were captured by Scanning Electron Microscope (SEM). The results revealed that the highest particles amount of MnO2 is 31,63 grams which is electrolyzed at 8 volts for 16 hours. The highest purity of MnO2 is 89,23% which is electrolyzed at 2 volts for 16 hours. The particles produced were α-MnO2 with a tetragonal crystal system and nearly spherical in shape with size particles ranged from 136,01-202,48 and 144-352 nm.